Editorial [Hot Topic: Oxidative Stress Induced-Metabolic Imbalance, Mitochondrial Failure, And Cellular Hypoperfusion As Primary Pathogenetic Factors For The Development Of Alzheimer Disease Which Can Be Used As An Alternate And Successful Drug Treatment Strategy: Past, Present And Future (Guest Editor: Gjumrakch Aliev)] - Aliev, Gjumrakch (CNS & Neurological Disorders - Drug Targets, 2011)
Stroke and arteriosclerosis with neurological consequences such as Alzheimer disease (AD) are two leading causes of age-associated disability, dementia, and death. The Center for Disease Control and Prevention and the National Center for Health Statistics recently reported that AD has surpassed diabetes as a leading cause of death. AD is now the sixth-leading cause of death in the United States. With our nation facing an unprecedented population shift of aging baby boomers–and AD poised to strike 10 million of them–it is clear this escalating epidemic must be addressed now with our help. Estimates for the US tell us that AD affects 4 million people (rising steeply from <1% of the population aged 65 to 40% of those aged 90) and costs 600 billion per year, which is equivalent to the total cost of stroke, heart disease, and cancer combined. Overall, there are no effective strategies for determining and controlling this devastating disease. Conventional wisdom for the last 20 years has decreed that AD is a ‘neurodegenerative’ disorder that is primarily caused by the abnormal deposition of a protein called ‘amyloid-beta’ (Aβ) in brain tissue. Neurodegenerative disorders are characterized by a loss of cognitive function and inappropriate death of nerve cells in areas of the brain that control such functions as memory and language. The trigger for nerve cell death is unknown in AD, as well as in other neurodegenerative conditions, in which memory decline is a prominent feature. The finding of Aβ deposition in AD brains after death led to the so-called “amyloid hypothesis”. For almost two decades now, the amyloid hypothesis has influenced and guided research in the field of AD dementia such that many researchers regard it as the gold standard of scientific investigation. Indeed, most of the literature claims that AD is caused by Aβ deposition within structures called senile plaques. The formation of these plaques are purported to lead to further abnormalities within the surrounding nerve cells, eventually killing them. However, there is little evidence to support this claim and ample evidence to question it. For example, the amyloid hypothesis has been criticized because research findings up to now have not generated any benefits in the clinical management and treatment of AD patients, nor have they advanced our understanding of how the elderly are preferentially affected. The three main flaws of the hypothesis appear to be that: (1) Aβ deposition has not been found to be toxic or to cause the damage and death of cerebrally located nerve cells in humans or animals; (2) the brains of many aged, but cognitively normal individuals show abundant Aβ-containing senile plaques but no clinical signs of AD; and (3) since there is general agreement that Aβ-containing senile plaques are the products of degenerating neurons, they can not be the cause, since it is axiomatic that a product is the result, not the cause of some activity. By contrast, there is now considerable and still growing evidence from the fields of epidemiology, pharmacology, neuroimaging, clinical medicine, microscopic anatomy/pathology, and molecular biology which indicate that non-genetic AD is an oxidative stress-induced mitochondrial disorder that affects cerebral vascular cells in addition to neurons and glia that exacerbates cerebral hypoperfusion. This evidence can be summarized as follows: (1) numerous epidemiologic studies link AD risk factors such as stroke, heart disease, hypertension, and atherosclerosis to reduced cerebral blood flow; (2) evidence that AD and vascular dementia (VaD), an acknowledged vascular disorder, share practically all the same risk factors and may benefit from the same treatments; (3) drug therapies reported to improve AD symptoms (including prescriptive drugs now available for AD) all increase blood flow to the brain; (4) people who are likely to develop AD but do not yet show signs of dementia can be identified by using brain blood flow measurements and brain positron emission tomography scans; (5) the clinical symptoms are very similar in most AD and VaD patients; (6) parallel abnormalities such as Aβ-laden plaques found in AD and VaD patients occur in both brain vessels and brain tissue; (7) low levels of brain blood flow in aged humans and animals can lead to abnormal cell metabolism, tissue damage, and memory problems independent of Aβ; (8) mild cognitive impairment (a term used to describe a preliminary stage leading to AD) can convert equally to AD or VaD; and (9) small vessel damage is present in the majority of AD brains after death. Based on these results, as well as a bare-bones examination of the literature, it is clear that no compelling evidence exists to conclude that Aβ deposition causes AD or that it results in significant damage to brain cells. Re-classification of AD from a neurodegenerative disorder to an oxidative stress-induced metabolic syndrome with mitochondrial failure that occurs within both cerebral blood vessels and neurons would steer researchers down the correct path and would be able to speed the development of truly beneficial treatments. It would be possible to improve patient management, provide earlier diagnoses, and reduce the number of AD cases in the future by aggressively treating the risk factors before they can turn into dementia. These initiating pathological events most likely occur several years before the clinical manifestation of the disease, implying that potential therapeutic interventions are currently being started too late to give beneficial results. Moreover, there is a growing body of evidence supporting the hypothesis that mild cognitive impairment is a prodromal phase of AD, since 80% of patients diagnosed with mild cognitive impairment develop the full blown manifestations of AD within 5-6 years. The articles compiled within this special issue highlight the most recent insights into the molecular mechanisms involved in the earliest stages of AD pathogenesis, namely that of oxidative stress-induced metabolic abnormalities, mitochondrial failure which initiates the energy crisis and vascular and cellular hypoperfusion, and lays out future potential treatment strategies based on these findings. Also discussed are the mutual pathogenic processes and antecedent biological markers shared between AD and other cardiovascular, cerebrovascular, and neurodegenerative diseases. I feel confident that elucidating the commonalities between these diseases will provide the necessary key to finally conquering AD.